A Giant Aggressive Angiomyxoma of the Pelvis Misdiagnosed as Incarcerated Femoral Hernia: A Case Report and Review of the Literature. (5th May 2016) - Sozutek, Alper; Irkorucu, Oktay; Reyhan, Enver; Yener, Kemal; Besen, Ali Ayberk; Erdogan, Kivilcim Eren; Gonlusen, Gulfiliz; Doran, Figen
Abstract : Aggressive angiomyxoma (AA) is an uncommon mesenchymal tumor that is mostly derived from the female pelvic and perineal regions. AA is a locally infiltrative slow growing tumor with a marked tendency to local recurrence. Painless swelling located around the genitofemoral region is the common symptom; thus, it is often misdiagnosed as a gynecological malignancy or a groin hernia. A 35-year-old female patient who previously underwent surgery for left femoral hernia operation resulting in surgical failure was reoperated for a giant AA located in the pelvis. The tumor was completely excised with free margins. Histopathologic examination revealed an AA. The tumor size was measured as 24 × 12 × 6 cm with a weight of 4.2 kg. Immunohistochemically, the cells show positive staining with vimentin, desmin, estrogen, and progesterone receptor. S100, MUC4, CD34, and SMA were negative in the tumor cells. AA should be considered in the differential diagnosis of any painless swelling located in the genitofemoral region, particularly in women of reproductive age. The principle treatment should be complete surgical excision with tumor-free margins. Long-term follow-up and careful monitoring are essential due to its high tendency of local recurrence in spite of wide excision of the tumor. Adjuvant antihormonal therapy yields promising results for preventing recurrence.